Water availability and food security challenges in Egypt - Hamza W.; Mason S. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
In Egypt, in order to meet the increased food needs, two basic strategies are possible: importing food or growing more food. Egypt imports about 236 m3 water per capita per year in the form of food. Different agriculture projects were established with the aim to enlarge the cultivated area and to guarantee sufficient production of the main crops. Based on the concept of re-use and efficiency increase, it is expected that the use of scientific knowledge, international experience and cooperation as well as advanced management tools should help in the sustainable planning of the future economy. Thus on the national level, re-use and efficient water utilization have the highest priority. According to Egyptian estimates, an additional 20.9 km3year-1 could be made available through recycling water, by changing irrigation techniques and adopting water efficient crops and cropping patterns. This is equal to 30 percent of the water that is used at present.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)